Maintaining, troubleshooting, automating in ArcGIS Server - Nelson, Steph A.; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"ArcGIS Server provides a backbone for web maps and applications. Users can publish data from shapefiles, files, and enterprise geodatabases to allow for customized display and access in web maps and applications. ArcGIS provides a scalable framework for implementing GIS solutions for a single user or many users on desktops, in servers, over the web, and in the field.This course will instruct viewers how to deploy ArcGIS Server, publish and consume services via ArcGIS and third-party platforms. It starts with optimizing and monitoring the services. After that, you'll learn how to configure a secure environment and control who has access to your services. In the third section, you'll understand how to automate common server administration and data management tasks using the ArcGIS REST API, ArcPy and command line utilities. in the last section of this course, address some common issues that arise with installing and administering your server and publishing your services. This series instructs viewers how to maintain, troubleshoot, and fine-tune your ArcGIS Server and services and automate server management tasks."--Resource description page.
Presenter, Steph A. Nelson.
Title from title screen (viewed January 12, 2018).
Date of publication from resource description page.
Keywords: ArcGIS; Geographic information systems -- Programming; Geographic information systems; Spatial data infrastructures; Electronic books